1998
DOI: 10.1111/j.1525-1470.1998.tb01362.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Clinical Pattern of Atopic Dermatitis in a North Indian Pediatric Population

Abstract: Various epidemiologic factors and clinical patterns of atopic dermatitis (AD) were evaluated in 672 children. Of these, 210 were infants (up to 1 year) and 462 were children. Mean age at onset and mean duration of the disease were 4.2 months and 3.3 months, respectively, in the "infantile AD" group. In the "childhood AD" group the corresponding figures were 4.1 years and 1.9 years. In both groups, patients from urban areas significantly outnumbered those from rural backgrounds. In the infantile AD group, the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Acute eczema was seen in 28.79%, subacute in 23.38%, chronic in 47.40% and follicular in 0.43% of the children. [12] Another hospital-based North Indian study later on documented an incidence of 29.9% of total patients. The population comprised of 125 patients, including 26 infants and 99 children, showing a mean duration of disease of 3 months in infants and 6 years in children.…”
Section: Epidemiology and Clinical Patternsmentioning
confidence: 99%
“…Acute eczema was seen in 28.79%, subacute in 23.38%, chronic in 47.40% and follicular in 0.43% of the children. [12] Another hospital-based North Indian study later on documented an incidence of 29.9% of total patients. The population comprised of 125 patients, including 26 infants and 99 children, showing a mean duration of disease of 3 months in infants and 6 years in children.…”
Section: Epidemiology and Clinical Patternsmentioning
confidence: 99%
“…Cold and dry weather increase the overall risk of flares in patients with AD and further increase its incidence and prevalence (Table ) . Accordingly, a higher prevalence of AD was found in American states with low humidity, low UV exposure, low outdoor temperature, use of indoor heating and frequent precipitation .…”
Section: Effect Of Seasonal and Climatic Variations On The Risk Of Dementioning
confidence: 99%
“…In the present study, the male to female ratio was 1.08:1. Previous studies have also reported a male predominance, i.e., 2.13:1 for infants and 1.09:1 for children, [10] 1.8:1, [12] 2.25:1 for infants and 1.6:1 for children, [13] 1.3:1 [14] and 1.56:1. [13] The mean age of onset in the present study was 2.49 years.…”
Section: Discussionmentioning
confidence: 96%
“…The corresponding figures in the childhood AD patients were 58% and 32.9%, respectively. [10] On the contrary, in the study by Dhar et al in different climatic conditions in Eastern India, 40% patients had aggravation during summers and only 15% had winter exacerbation. [14] AD is more common in the urban than in the rural set up.…”
Section: Majority Of the Patients In A Study By Sarkar Andmentioning
confidence: 90%
See 1 more Smart Citation